Media consumption and political participation of young university students durign Mexican presidential election, 2018 - De la Garza Montemayor, Daniel (2018)
Several academic studies have confirmed that young university students are using social media to get information about what is happening with their communities. This article explores what are the levels of consumption of traditional media, as well as digital media of young Mexican students from different regions of this country. The research was carried out in the context of the presidential elections of 2018. More than 1200 questionnaires were applied on line. The main objective of the research is to understand both traditional and digital media consumption and how these factors affect the political participation of this group of the population, inside and outside the internet. Among the main results expected to find a growing trend in the use of digital media to the detriment of the traditional, as well as a close relationship between political participation and media consumption.